Penerapan ICT dalam Pelayanan Publik di Kabupaten Bantul - Supardal Supardal (Otoritas : Jurnal Ilmu Pemerintahan, 2016)
The transformation of the bureaucracy into a necessity. One way transformation of the bureaucracy in the public service is the application of information and communications technology (ICT) in the public service. Information Communication Technology innitiative and application in local govern-ment should transform local government bureaucracy in public service. In Bantul, however, ICT in-nitiative and application has not successfully transformed local government bureaucracy in public service. This study will assessed on the impact of ICT innitiative and application on the bureaucracy transformation in public service. The mix research method is choosen in order to answer and analy-sis the phenomena in depht. The research found that the influence of the ICT’s innitiative on the bureaucracy transformation in the Bantul District is only 18 %. The low effect of the implementa-tion of the system of ICT in those cities is affected by strong patronage culture, the hierarchical organizational structure and centralized regulation on local government structure, low capacity e-leadership of middle range leader, and no delegation from top leader to middle management.Transformasi birokrasi menjadi keharusan. Salah satu cara transformasi birokrasi dalam pelayanan publik adalah penerapan teknologi informasi dan komunikasi (ICT) dalam pelayanan publik. Praksarsa dan implementasi Teknologi Informasi Komunikasi di pemerintah daerah harus mengu-bah birokrasi pemerintah daerah dalam pelayanan publik. Di Bantul, bagaimanapun, Praksarsa dan Implementasi ICT belum berhasil mengubah birokrasi pemerintah daerah dalam pelayanan publik. Penelitian ini akan dinilai pada dampak Prakarsa dan Implementasi ICT pada transformasi birokrasi dalam pelayanan publik. Metode penelitian campuran yang terpilih untuk menjawab dan analisis fenomena. Penelitian ini menemukan bahwa pengaruh Prakarsa ICT pada transformasi birokrasi di Kabupaten Bantul hanya 18%. Pengaruh rendah dari pelaksanaan sistem ICT di kota-kota dipengaruhi oleh budaya yang Patronase yang kuat, struktur organisasi hirarkis dan regulasi terpusat pada struktur pemerintah daerah, kapasitas rendah e-kepemimpinan middle leader, dan tidak ada delegasi dari top leader ke middle management.